What is wrong with populism? - Kulenović, Enes, politolog (Array, 2021)
The main goal of this article is to explore the relationship between populism and representative democracy. The paper is divided into two parts. In the first part, the paper offers a detailed analysis of the three criticisms of populism and the implications these criticisms have on our understanding of representative democracy. First, it addresses the argument that populism inevitably relies on demagogy and it examines the inference this argument has on the concept of political representation in democracy. Second, it discusses the claim that populism relies on the oversimplification of political issues and what this claim reveals about the democratic ideal of the informed and politically responsible voter. The third criticism deals with the anti-pluralist character of populist politics, which, the paper argues, can also be extended to the concept of popular sovereignty itself. In the second part, the article looks more closely at the relationship between populism and representative democracy. Relying on the insights from the first part, it examines different institutional restraints on the will of the majority and how populism redefines these restraints as anti-democratic and elitist barriers to popular will. Finally, the paper questions the prevailing view that sees populism as a phenomenon arising from the tension between liberal and democratic principles within representative democracy and offers an alternative framework for understanding the relationship between populism and democracy.